P092 Microarray pathway analysis comparing baricitinib and adalimumab in moderate to severe rheumatoid arthritis from a phase 3 study. (21st February 2018) - Emery, P; Taylor, PC; Weinblatt, ME; Tanaka, Y; Keystone, EC; Dow, ER; Higgs, R; Macias, WL; Rocha, G; Rooney, TP; Schlichting, DE; Zuckerman, SH; et al.
Abstract : Introduction: In RA-BEAM (NCT01710358 ), baricitinib (BARI), an oral selective inhibitor of Janus kinase (JAK) 1 and JAK 2, showed significant improvements in patients (pts) with active RA who had an inadequate response to methotrexate compared to placebo (PBO) or adalimumab (ADA). Objectives: To analyse pathways modulated by BARI compared with ADA (both relative to PBO) through 12 wks of treatment. Methods: Pts (n=1307) were randomised 3:3:2 to PBO, BARI 4 mg QD, ADA 40 mg q 2 wks. Total RNA extracted from whole blood drawn at baseline (BL), wk4, and wk12 was analysed using the GeneChip Human Transcriptome Array 2.0 (Affymetrix). Data were analysed using a mixed effects model on a log2 transformed response. Results: There was little overlap of the immune pathways modulated by both BARI and ADA at wk4 with no significant overlap by wk12. BARI downregulated JAK/Signal Transducer and Activator of Transcription (STAT) signalling pathways, like those induced by IFNs, IL-6, GM-CSF, IL-5, and IL-3. Expression of interferon responsive genes (IRGs) was downregulated by BARI and upregulated by ADA. BARI reduced IRGs by 75% at wk4 in pts that had high IFN gene expression at BL. ADA modulated complement pathways. Of interest, STAT transcripts were reduced at wk4 by BARI (STAT1, 2, 3, 5A, 5B, 6); by wk12 several STATs (STAT 1, 2, 5A) did not differ from PBO. Additional differences were noted in the number of genes modulated by each treatment. BARI modulated more genes than ADA at wks 4 and 12; BARI resulted in more gene modulation at wk12 than at wk4, whereas ADA gene modulation was similar at wks 4 and 12. Both the numbers and types of genes modulated by BARI diverged further from ADA at wk12 than at wk4. Conclusions: Gene expression profiling showed significant differences between BARI and ADA treatments. BARI and ADA modulated JAK/STAT or complement pathways, respectively, and the drugs had opposite effects on interferons, indicating different and possibly complementary mechanisms of action of each targeted therapy. Acknowledgements: Study support: Eli Lilly and Company and Incyte Corporation. Encore of ACR/ARHP-2017 Annual Scientific Meeting, Nov 4–8, 2016; San Diego, CA, USA. Disclosure of interest: None declared